Anti-Cancer Activity of As4O6 and its Efficacy in a Series of Patient-Derived Xenografts for Human Cervical Cancer - Joseph J. Noh; Myeong-Seon Kim; Young-Jae Cho; Soo-Young Jeong; Yoo-Young Lee; Ji-Yoon Ryu; Jung-Joo Choi; Illju Bae; Zhaoyan Wu; Byoung-Gie Kim; Jae Ryoung Hwang; Jeong-Won Lee (MDPI AG, 2020)
Purpose: To investigate the anti-cancer effects of tetraarsenic hexoxide (TAO, As4O6) in cervical cancer cell lines and in a series of patient-derived xenograft (PDX) mouse models. Methods: Human cervical cancer cell lines, including HeLa, SiHa and CaSki, and human umbilical vein endothelial cells (HUVECs), were used to evaluate the anti-cancer activity of TAO. Cellular proliferation, apoptosis, and enzyme-linked immunosorbent assay (ELISA) for matrix metallopeptidase 2 (MMP-2) and 9 (MMP-9) were assessed. The tumor weights of the PDXs that were given TAO were measured. The PDXs included primary squamous cell carcinoma, primary adenocarcinoma, recurrent squamous cell carcinoma, and recurrent adenocarcinoma. Results: TAO significantly decreased cellular proliferation and increased apoptosis in cervical cancer cell lines and HUVEC. The functional studies on the cytotoxicity of TAO revealed that it inhibited the activation of Akt and vascular endothelial growth factor receptor 2 (VEGFR2). It also decreased the concentrations of MMP-2 in both cervical cancer cell lines and HUVECs. Active caspase-3 and p62 were both increased by the treatment of TAO, indicating increased rates of apoptosis and decreased rates of autophagy, respectively. In vivo studies with PDXs revealed that TAO significantly decreased tumor weight for both primary squamous cell carcinoma and adenocarcinoma of the cervix. However, this anti-cancer effect was not seen in PDXs with recurrent cancers. Nevertheless, the combination of TAO with cisplatin significantly decreased tumor weight in PDX models for both primary and recurrent cancers. Conclusions: TAO exerted inhibitory effects on angiogenesis, cellular migration, and autophagy, and it showed stimulatory effects on apoptosis. Overall, it demonstrated anti-cancer effects in animal models for human cervical cancer.